2012
DOI: 10.1002/jcp.22975
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress regulates expression of death‐associated protein kinase in suppressing TNFα‐induced endothelial apoptosis

Abstract: Death associated protein kinase (DAPK) is a positive regulator in tumor necrosis factor α (TNFα)-induced apoptotic pathway, and DAPK expression is lost in cancer cells. In the vasculature, misdirected apoptosis in endothelial cells leads to pathological conditions such as inflammation and physiological shear stress is protective against apoptosis. Using bovine aortic endothelial cells, we found that DAPK expression increased, while the auto-inhibitory phosphorylation of serine 308 decreased with shear stress a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 36 publications
5
21
0
Order By: Relevance
“…Previous studies have shown that shear stress can affect apoptosis in different cell types such as endothelial cells [6668], osteoblasts [8], and tumor cells [9]. In the cornea, Yamamoto et al .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that shear stress can affect apoptosis in different cell types such as endothelial cells [6668], osteoblasts [8], and tumor cells [9]. In the cornea, Yamamoto et al .…”
Section: Resultsmentioning
confidence: 99%
“…A previous study identified that DAPK functioned as a positive mediator of apoptosis induced by various stimuli, including TNF-α, interferon-γ and p53 (29). It was previously reported that DAPK activity may be involved in TNF-α-induced apoptotic pathways in bovine aortic endothelial cells (20). To the best of our knowledge, the present study is the first to reported that Hcy treatment increased mRNA and protein DAPK expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…DAPK is upstream of the caspases, with the exception of caspase 8, and may induce caspase-independent cell death or autophagy. Previous studies have determined that DAPK contributed to shear stress-induced endothelial apoptosis (20,21). However, the importance of DAPK in Hcy-induced apoptosis in endothelial cells remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Tumor necrosis factor (TNF) α activates PKCζ in EC 1 and induces its apoptosis, 3,4 which contributes to vascular diseases such as atherosclerosis. 5 We are, therefore, interested in the mechanism of PKCζ-dependent EC apoptosis in response to TNFα stimulation.…”
mentioning
confidence: 99%